Rubber Structure under Dynamic Loading – Computational Studies - BARANOWSKI, Paweł; GIELETA, Roman; MAŁACHOWSKI, Jerzy; MAZURKIEWICZ, Łukasz (Engineering Transactions, 2014)
This study focuses on the rubber structure behaviour assessment under dynamic load- ing using numerical methods. Dynamic simulations of the TNT explosion under the tire- suspension system were performed using the explicit LS-Dyna code using Arbitrary Lagrangian- Eulerian formulation with Jones Wilkins Lee (JWL) equation defining the explosive material. During analyses two different constitutive materials were used: Mooney-Rivlin without rate- dependency and Ogden rubberlike material (MAT 181 Simplified Rubber) which includes strain rate effects. Consequently, tire rubber material behaviour was investigated and compared for two simulated cases.